Eastern Association for the Surgery of Trauma and Society of Trauma Nurses advanced practitioner position paper: Optimizing the integration of advanced practitioners in trauma and critical care. Issue 1 (July 2017) - Messing, Jonathan; Garces-King, Jasmine; Taylor, Dennis; van Horn, Jonathan; Sarani, Babak; Christmas, A. Britton
Abstract : ABSTRACT: Nurse practitioners and physician assistants, collectively known as advanced practitioners (APs), enhance the provision of care for the acutely injured patient. Despite their prevalence, institutions employ, train, and utilize these providers with significant variability. The Eastern Association for the Surgery of Trauma, the Society of Trauma Nurses, and the American Association of Surgical Physician Assistants acknowledge the value of APs and support their utilization in the management of injured and critically ill patients. This position paper offers insight into the history of, scope of practice for, and opportunities for optimal utilization of APs in trauma, critical care, and acute care surgery services.